1997
DOI: 10.2307/1244272
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Models of Japanese Demand for Fish

Abstract: Given a relative lack of knowledge about Japanese consumer preferences for fish, Japanese fish demand is modeled using both Marshallian (ordinary) and inverse demand systems, each of which nests a number of competing specifications. Results indicate that the inverse demand systems dominate the ordinary demand systems in forecasting performance and in nonnested tests. The inverse system suggests that Japanese fish prices are less responsive to changes in consumption than found in previous studies. Copyright 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…On perishable product markets, where products cannot be stored, quantity is usually taken as given exogenously, so price is determined exclusively by demand (see for instance Huang, 1988;Barten and Bettendorf, 1989;Eales et al, 1997). Moreover, all the regulations and interventions on the part of the authorities (TACs, control of fishing effort, limitation on the entry of vessels, etc.)…”
Section: Empirical Specification and Estimation Of The Demand Functionmentioning
confidence: 99%
“…On perishable product markets, where products cannot be stored, quantity is usually taken as given exogenously, so price is determined exclusively by demand (see for instance Huang, 1988;Barten and Bettendorf, 1989;Eales et al, 1997). Moreover, all the regulations and interventions on the part of the authorities (TACs, control of fishing effort, limitation on the entry of vessels, etc.)…”
Section: Empirical Specification and Estimation Of The Demand Functionmentioning
confidence: 99%
“…However, matching historical weather data from weather stations to certain fish stocks at a given point in time proved to be infeasible. I used other standard variables in the literature as instruments, namely diesel prices, twelve-month lagged variables and monthly dummies, see e.g., Eales and Unnevehr (1993), Eales et al (1997), Matsuda (2005) or Park et al (2004). The coefficient estimates from the 3SLS estimator were then compared with the estimates from the SUR estimator and systematic differences were tested for.…”
Section: Exogeneity Of Quantitymentioning
confidence: 99%
“…One of the most cited papers is Barten and Bettendorf's (1989) empirical study of fish landed in Belgian ports. From a theoretical perspective, the general trend has been to move from estimating and improving upon single inverse demand models e.g., Moschini and Vissa (1992) and Holt and Goodwin (1997) to nesting existing inverse demand systems in more general models to see which one best fits the data e.g., Eales et al (1997) and Brown et al (1995). Besides fish, the most common markets that have been the subject of study under inverse demand are meat, fruit and vegetables.…”
mentioning
confidence: 99%
“…Anderson (1980) deduced the mathematical framework for inverse demand systems, Barten and Bettendorf (1989) introduced the Rotterdam model in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Furthermore, Eales, Durham and Wessels (1997) estimated both ordinary and inverse demand systems for fish in Japan. They found that for fresh products, the quantity available in any month must be consumed and so price must adjust.…”
Section: Introductionmentioning
confidence: 99%